(untitled) (Annals of Medical Research, 2021)
Aim: Estrogen receptor-α(ERα) and Progesterone receptor(PR) were studied in 58 patients who were diagnosed as papillary thyroid carcinoma in our hospital between 2011 and 2013.ERα and PR expression patterns were compared according to age, sex, tumor subtype, metastasis, focality and tumor size.